Musculoskeletal Complications Associated with Vitamin D Deficiency and Review of Current Interventions (Global Journal of Medical Research, 2023)
Background Hypovitaminosis D is commonly prevalent in older population world over leading to increased levels of bone resorption reduced bone mass often resulting inosteoporosis and increased chances of falls and fractures In children vitamin D deficiency is known to cause rickets due to hypomineralization of bone Methods PubMed EMBASE Cochrane Library and Google Scholar databases were searched from database inception until May 20 2022 Searches were performed between January 2022 and May 2022
Keywords: vitamin D; musculoskeletal; osteoporosis; rickets; bone fracture; bone density